PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI REFLEKSI KELAS XI OTKP 4 SMK NEGERI 2 PALU - Hamsiana, Hamsiana; Hasbi, Muh.; Sukayasa, Sukayasa; Lefrida, Rita (Aksioma, 2025)
This study aims to describe the application of cooperative learning model type think pair share in improving student learning outcomes on reflection material in class XI OTKP 4 SMK Negeri 2 Palu. The research method used is class action research (PTK). This research was conducted in two cycles, each cycle consisting of two meetings. This research design refers to the research design of Kemmis and Mc. Taggart's research design, namely (1) planning, (2) action implementation and observation and (3) reflection. Data analysis in this study used a qualitative approach. The data analysis used refers to Paizaluddin and Ermalinda (2013) who say that the analysis of data obtained in class action research is generally analyzed through qualitative descriptive. The data collection methods in this study include observation, interviews and field notes. The results showed that student learning outcomes could be improved by applying the cooperative learning model of think pair share (TPS) type in class XI OTKP 4 SMKN 2 PALU. This can be seen after applying the think pair share (TPS) learning model, in the first cycle the student learning outcomes that reached completeness were only 51.85%. Then in the second cycle the student learning outcomes that reached completeness were 76.67%. so it can be concluded that the application of the cooperative learning model type think pair share (TPS) can improve student learning outcomes on reflection material in class XI OTKP 4 SMK Negeri 2 Palu.